Preferences of pregnant women in the choice of mode of delivery - Martins, Ivani Pose; Santos, Jeniffer Stefany de Souza; Silva, Liliane Aparecida da Costa; Vieira, Lívia Maria; Leal, José Carlos; Mota, Sandra de Almada; Barbosa, Fernando Sérgio (Seven Editora, 2024)
Studies reveal that most women have a preference for vaginal delivery both in public health and in the private sector, however, the private sector has more than twice as many surgical deliveries shaped by the interventionist conduct of the physician. Among the factors that are pointed out in most studies to justify the increasing frequency of cesarean sections are social, demographic, and cultural factors, associated with the mother's request for the type of delivery, and factors associated with the care model developed. Based on the above, it is intended, based on the data collected, to investigate the perception of pregnant women in relation to the types of delivery and what guidance they received during prenatal care. To this end, a quantitative-qualitative, cross-sectional descriptive study will be carried out in pregnant women treated at the UBS in the municipality of Iguatama-M. The results show that pregnant women have a preference for cesarean delivery, with significant relevance to the variables "it helps to reduce maternal stress during childbirth by conveying an idea of a fully controlled environment, where everything occurs in a previously stipulated way"; "short labor of predictable duration"; "active participation of the mother". It was concluded that 56% of the participants preferred cesarean section because it was quick to recover. DOI:https://doi.org/10.56238/sevened2024.007-059